Preparation and evaluation of famotidine nanosuspension - Marwa M. Malik; Nidhal K Maraie (College of Pharmacy / Mustansiriyah University, 2018)
Famotidine (FM) is a potent H2-receptor antagonist used for the treatment of peptic ulcer. It has a low and variable bioavailability which is attributed to its low water solubility. There are many methods used to increase dissolution rate of drug and in this study, the dissolution of the drug was enhanced by the preparation of nanosuspension. Famotidine nanosuspension was prepared by antisolvent precipitation method, where famotidine dissolved in methanol at room temperature and emptied into water containing different types of stabilizers (single and in combination). The optimum formula (F9) was selected according to particle size (362.8nm) and release profile (80 % of drug release within the 10 minutes) in comparison to pure famotidine powder release. The influence of formulation variables like the type and concentration of stabilizers Polyvinyl pyrrolidone K30, polyvinyl alcohol and poloxamer 188 (PVP K-30, PVA and poloxamer 188) in addition to combination of stabilizers on particle size of drug nanosuspensions were studied. The result showed that single stabilizer (poloxamer 188) has perfect surface affinity and could form a substantial mechanical and thermodynamic barrier at the interface of dug molecule. As the concentration of stabilizer increases the particle size decreases at fixed drug concentration (drug: stabilizer ratio 1:2).